Metal solidification–nucleation–rate model under coupling effects of shearing flow and vibration. Issue 2 (22nd January 2016) - Wang, X.; Guan, R.G.; Guo, N.; Zhao, Z.Y.; Zhang, Y.; Su, N.
Abstract : This paper proposes the influence factors of coupling effects of shearing flow and vibration on diffusion coefficient and critical nucleation energy during metal solidification. Based on this proposal, a metal solidification–nucleation–rate model under coupling effects of shearing flow and vibration is established. Verification experiment using Al–7Si alloy is carried out. When vibration frequency and melt flow velocity are zero, the results calculated by the above model agree with that calculated by Turnbull's theory. The results calculated by the above model under coupling effects of shearing flow and vibration agree with the experimental results, with the error within 0·2–14·3%. So the established model can calculate and explain the nucleation rate of melt under coupling effects of shearing flow and vibration.